Democracy Under Attack: Challenges of Addressing Ethical Issues of AI and Big Data for More Democratic Digital Media and Societies - Christodoulou, Eleni; Iordanou, Kalypso (Frontiers in Political Science, 2021)
The potency and potential of digital media to contribute to democracy has recently come under intense scrutiny. In the context of rising populism, extremism, digital surveillance and manipulation of data, there has been a shift towards more critical approaches to digital media including its producers and consumers. This shift, concomitant with calls for a path toward digital well-being, warrants a closer investigation into the study of the ethical issues arising from Artificial Intelligence (AI) and Big Data. The use of Big Data and AI in digital media are often incongruent with fundamental democratic principles and human rights. The dominant paradigm is one of covert exploitation, erosion of individual agency and autonomy, and a sheer lack of transparency and accountability, reminiscent of authoritarian dynamics rather than of a digital well-being with equal and active participation of informed citizens. Our paper contributes to the promising research landscape that seeks to address these ethical issues by providing an in-depth analysis of the challenges that stakeholders are faced with when attempts are made to mitigate the negative implications of Big Data and AI. Rich empirical evidence collected from six focus groups, across Europe, with key stakeholders in the area of shaping ethical dimensions of technology, provide useful insights into elucidating the multifaceted dilemmas, tensions and obstacles that stakeholders are confronted with when being tasked to address ethical issues of digital media, with a focus on AI and Big Data. Identifying, discussing and explicating these challenges is a crucial and necessary step if researchers and policymakers are to envisage and design ways and policies to overcome them. Our findings enrich the academic discourse and are useful for practitioners engaging in the pursuit of responsible innovation that protects the well-being of its users while defending the democratic foundations which are at stake.